Learning, adapting and leading: a Malay woman experience - Alias, Siti Noormi; Tg. Abdullah, Tg. Tijan Marjani (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Despites of the fact that Malaysian public sector is still dominated by male counterpart, however, there are still a few “iron ladies” who manage to escape the glass ceiling, be at the top, and successfully lead the organization. Even though increasing numbers of both quantitative and qualitative studies have been conducted, however studies that exposing an individual experience from specific racial perspectives are still limited. A qualitative single-case study research approach is used in this study to examine the approaches used by one of top-level Malay woman administrator to break male-centric realm in one of Malaysian higher education government agency. Born and raised from a gender-neutral family, obtained academic degrees and work in male-dominated field, and spent few years working as an engineer shaped the way she thought and behaved at work. The findings in the study indicates that excellent work performance shown until it has been recognized by the former male leader becomes the greatest approach used by the informant to break the patriarchal monopoly. The findings also suggest the non-existence of gender discrimination issue among Malaysian government agency. Implications and recommendation towards future studies are also outlined.